Turkey tail mushroom (Trametes versicolor) : an edible macrofungi with immense medicinal properties - Olaide Olawunmi, Ajibola; Cirilo, Nolasco-Hipolito; Octavio, Carvajal Zarrabal; Shanti Faridah, Salleh; Gbadebo, Clement Adeyinka; Stephen, A Adefegha; Mirja, K. Ahmmed; Kazi, Sumaiya; Raymond, Thomas (Elsevier Ltd., 2024)
Macrofungi, commonly known as mushrooms, are not only considered functional foods for supplying essential nutritional ingredients but also a good source of physiologically beneficial medicines. Trametes versicolor, referred to as turkey tail’s Mushroom or Yun Zhi in China, is an edible mushroom that has extensive historical usage in conventional and traditional Chinese medicine. This mushroom contains an abundance of physiologically bioactive compounds, most notably β-glucan polysaccharides, which are responsible for antioxidant, neuroprotection, hypolipidemic effects, immune-modulating effects, and anticancer effects. Trametes versicolor has also been revealed to have wound healing, antidiabetic, antimicrobial, antifibrotic, neurotrophic, and anti-inflammatory effects among other therapeutic efficacies. This review paper has overviewed the recent advances in the research and study on Trametes versicolor and discussed the potential health- promoting properties of this exotic macrofungi, with the recognition of bioactive and polysaccharide constituents responsible for these medicinal agents.